Reduced Effectiveness and Comparable Safety in Biweekly vs. Weekly PEGylated Recombinant Human Growth Hormone for Children With Growth Hormone Deficiency: A Phase IV Non-Inferiority Threshold Targeted Trial - Sun, Chengjun; Lu, Biao; Liu, Yu; Zhang, Yaqin; Wei, Haiyan; Hu, Xu; Hu, Pei; Zhao, Qian; Liu, Yanling; Ye, Kan; Wang, Kan; Gu, Zaiyan; et al. (Frontiers in Endocrinology, 2021)
Context: Long-acting recombinant human growth hormone (rhGH) has transformed growth hormone deficiency (GHD) treatment. However, the possibility and rationality for flexible time regimen are pending. Objective: We studied the efficacy of biweekly versus weekly PEGylated rhGH (PEG-rhGH) therapy in GHD children. Design, Setting, and Patients: This multicentre, phase IV trial with a noninferiority threshold ≥20% enrolled 585 Tanner stage I GHD children. Intervention: Subjects randomly received 0.20 mg/kg once weekly or biweekly PEG-rhGH, or 0.25 mg/kg.w rhGH once daily for 26 weeks. Main Outcome Measure: The primary outcome was height standard deviation scores for chronological age (HtSDSCA) at week 26. Safety included adverse events (AEs), IGF2 and IGFBP2 changes. Results: At week 26, the median HtSDSCA changed from -2.75, -2.82, and -2.78 to -2.31, -2.43, and -2.28 with weekly and biweekly PEG-rhGH, and daily rhGH, respectively. The difference in HtSDSCA was 0.17±0.28 between weekly and biweekly PEG-rhGH, and 0.17±0.27 between daily rhGH and biweekly PEG-rhGH, failing the non-inferiority threshold. Nevertheless, the height velocity of children receiving biweekly PEG-rhGH reached 76.42%-90.34% and 76.08%-90.60% that of children receiving weekly PEG-rhGH and daily rhGH, respectivley. The rate of AEs was comparable among the groups. No statistical difference was observed in IGF-2 and IGFBP-2 levels among the groups. IGFBP-2 levels decreased over time in all groups, with no notable difference in IGF-2 and IGFBP-2 change. Conclusions: Although notably promoted height velocity, biweekly PEG-rhGH failing the non-inferiority threshold as compared to either weekly PEG-rhGH or daily rhGH. Compared with short-term rhGH, long-acting PEG-rhGH did not significantly increase tumor-associated IGF-2 and IGFBP-2 expressions. (clinicaltrials.gov number NCT02976675).